2019
DOI: 10.1002/jcla.23166
|View full text |Cite
|
Sign up to set email alerts
|

Interactive association of baseline and changes in serum uric acid on renal dysfunction among community‐dwelling persons

Abstract: Background: Chronic kidney disease (CKD) is a major public health concern. Baseline serum uric acid (SUA) levels were independently associated with incident renal dysfunction, but whether baseline and changes in SUA produce an interactive effect on renal dysfunction remains unclear. Methods:The subjects comprised 460 men aged 68 ± 10 (mean ± standard deviation) years and 635 women aged 68 ± 9 years from a rural village. We have found participants who underwent a similar examination 3 years later, and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Moreover, elevated SUA change was reported to predict rapid eGFR decline (OR: 2.62; 95% CI: 2.22–3.12) significantly, and new‐onset kidney disease (OR: 2.16; 95% CI: 1.93–2.42) among Chinese elderly population. The finding was well aligned with the other two longitudinal research studies, which reported that elevated SUA change was an important risk factor for the renal function decline among the Japanese young population 19 and Japanese elderly community‐dwelling persons 10 . Our research also found that elderly people with elevated SUA change from the normal group to the hyperuricemia group witnessed the highest decrease of eGFR after the 5‐year follow‐up than participants in the other groups, which further confirmed the significant relationship between elevated SUA change and eGFR decline over 5 years ( r = −0.407, P < 0.001) in the research.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Moreover, elevated SUA change was reported to predict rapid eGFR decline (OR: 2.62; 95% CI: 2.22–3.12) significantly, and new‐onset kidney disease (OR: 2.16; 95% CI: 1.93–2.42) among Chinese elderly population. The finding was well aligned with the other two longitudinal research studies, which reported that elevated SUA change was an important risk factor for the renal function decline among the Japanese young population 19 and Japanese elderly community‐dwelling persons 10 . Our research also found that elderly people with elevated SUA change from the normal group to the hyperuricemia group witnessed the highest decrease of eGFR after the 5‐year follow‐up than participants in the other groups, which further confirmed the significant relationship between elevated SUA change and eGFR decline over 5 years ( r = −0.407, P < 0.001) in the research.…”
Section: Discussionsupporting
confidence: 88%
“…The finding was well aligned with the other two longitudinal research studies, which reported that elevated SUA change was an important risk factor for the renal function decline among the Japanese young population 19 and Japanese elderly community-dwelling persons. 10 Our research also found that elderly people with elevated SUA change from the normal group to the hyperuricemia group witnessed the highest decrease of eGFR after the 5-year follow-up than participants in the other groups, which further confirmed the significant relationship between elevated SUA change and eGFR decline over 5 years (r = À0.407, P < 0.001) in the research. We observed a stronger inverse correlation between SUA change and eGFR decline in women (r = À0.406, P < 0.001) than in men (r = À0.355, P < 0.001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A recent meta‐analysis revealed a direct relationship between elevated baseline SUA levels and incident CKD 1 . Longitudinal changes in SUA are interactively and independently associated with declining renal function in community‐dwelling older adults 2 …”
Section: Introductionmentioning
confidence: 99%